Relationship between physical fitness, ski technique and racing results of young alpine ski racers - Mildner, E.; Barth, M.; Ehn, G.; Kriebernegg, R.; Staudacher, A.; Raschner, C. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The demands of alpine skiing are complex and require special abilities. Currently one publication is known examining the relationship between anthropometric, motor characteristics and ranking position in 13-16 year old skiers (Álvarez-San Emeterio & González-Badillo, 2010). No data is available for younger skiers. The Austrian Ski Federation initiated the Kids Cup in 2004/05 as a talent scouting tool for 10-11 year old ski racers. The aim of this study was to analyse correlations between race results, ski technique and physical fitness at the final races of the Kids Cup 2009 & 2010.